2006
DOI: 10.1503/cmaj.051668
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune pancreatitis associated with renal lesions mimicking metastatic tumours

Abstract: A 52-year-old previously healthy man experienced a 30-pound weight loss over 2 months. The patient was newly diagnosed with diabetes mellitus, and an abdominal ultrasound identified a pancreatic mass. Clinical history included crampy abdominal discomfort localized to the right lower quadrant, which had started 2 months earlier. No other symptoms suggestive of biliary obstruction or pancreatic insufficiency were present. Past medical history included asthma but was otherwise unremarkable, with no history of alc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 18 publications
2
21
0
Order By: Relevance
“…IgG4-RKD is a new clinical entity in the field of nephrology, unrecognized before 2004, when the notion gradually emerged of it being an extrapancreatic manifestation of AIP [2][3][4][5][6][7][8][9][10][11][20][21][22][23][24][25]. This disease has many features helping to distinguish it from other types of TIN radiographically [26][27][28][29][30] and pathologically [11,21], and early detection provides the best chance for preservation of renal function because of its good responsiveness to corticosteroid therapy [2][3][4][5][6][7][8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IgG4-RKD is a new clinical entity in the field of nephrology, unrecognized before 2004, when the notion gradually emerged of it being an extrapancreatic manifestation of AIP [2][3][4][5][6][7][8][9][10][11][20][21][22][23][24][25]. This disease has many features helping to distinguish it from other types of TIN radiographically [26][27][28][29][30] and pathologically [11,21], and early detection provides the best chance for preservation of renal function because of its good responsiveness to corticosteroid therapy [2][3][4][5][6][7][8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…In the early reported cases, the development of renal dysfunction and/or proteinuria during the clinical course of AIP was the clue to the presence of renal involvement, and renal biopsy revealed tubulointerstitial nephritis (TIN) and fibrosis with dense infiltration of IgG4-positive plasma cells [2][3][4]. Thereafter, incidentally-detected IgG4-RKD cases in the course of close examination of AIP [5][6][7] or chronic sclerosing sialadenitis and dacryoadenitis [8] using enhanced computed tomography (CT) have been additionally accumulated. Recently, IgG4-RKD without AIP or chronic sclerosing sialadenitis and dacryoadenitis has also been reported [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical manifestations involve the pancreas, biliary tree, gallbladder, salivary glands, retroperitoneum, kidneys, lungs, and prostate. The renal lesions of patients with IgG4-related disorders are known to include tubulointerstitial nephritis or sometimes a renal pseudotumor (21,22). Takahashi et al (22) reported that 14 out of 40 AIP patients (35%) had renal involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Takahashi et al (22) reported that 14 out of 40 AIP patients (35%) had renal involvement. There have been several case reports of tubulointerstitial nephritis associated with a high serum IgG4 level and almost all of these patients showed infiltration of IgG4-positive cells into the renal interstitium (21,(23)(24)(25). On the other hand, it is interesting that decreased levels of complement and membranous glomerulonephropathy have been found in some cases of interstitial nephritis associated with IgG4-related disorders (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Renal lesions of the disease have been reported recently, most commonly they consist of tubulointerstitial nephritis (6,23,(27)(28)(29) (28,30,31). Plasma cells infiltrating the interstitium show strong immunoreactivity to IgG4 (21, 28, 30-32).…”
Section: Aip Is Diagnosed Based On the Presence Of Diffuse Swelling Omentioning
confidence: 99%